2014
DOI: 10.1038/nature13266
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast X-ray probing of water structure below the homogeneous ice nucleation temperature

Abstract: Water has a number of anomalous physical properties, and some of these become drastically enhanced on supercooling below the freezing point. Particular interest has focused on thermodynamic response functions that can be described using a normal component and an anomalous component that seems to diverge at about 228 kelvin (refs 1-3). This has prompted debate about conflicting theories that aim to explain many of the anomalous thermodynamic properties of water. One popular theory attributes the divergence to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

34
427
3
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 421 publications
(477 citation statements)
references
References 29 publications
34
427
3
10
Order By: Relevance
“…Thus, the experimentally inaccessible supercooled liquid region is now widely known as "no-man's land" [216], although there have been efforts to overcome the difficulty by either strong spatial confinement [217,218], mixing an anti-freezing component [219,220], or rapid cooling [221].…”
Section: Local Structural Ordering and Homogeneous Crystal Nucleationmentioning
confidence: 99%
“…Thus, the experimentally inaccessible supercooled liquid region is now widely known as "no-man's land" [216], although there have been efforts to overcome the difficulty by either strong spatial confinement [217,218], mixing an anti-freezing component [219,220], or rapid cooling [221].…”
Section: Local Structural Ordering and Homogeneous Crystal Nucleationmentioning
confidence: 99%
“…Sellberg et al 21 used a fast free-electron X-ray laser technique to study the structure of water at the 100 fs time scale in micrometer-sized droplets down to about 227 K and found that the molecular nearest-neighbor coordination of water molecules increases sharply. These observations confirmed similar computational findings that there is a sharp increase in the fraction of four-coordinate water molecules in the homogeneous nucleation regime.…”
Section: Introductionmentioning
confidence: 99%
“…Deposition of a fresh layer of soot before each trial effectively isolated the droplet from any unintended ice nuclei on the substrate (the soot itself remained inactive as nucleus down to droplet temperatures of approximately −15 • C). When the chamber is evacuated, a water droplet here rapidly cools to sub-freezing temperatures by evaporative cooling and, if nothing is done to prevent it, would spontaneously freeze [26,27]. However, unrestricted evaporative cooling gives very little control over the temperature profile in the drop during the experiment.…”
mentioning
confidence: 99%